2017
DOI: 10.7203/ciriec-e.88.9107
|View full text |Cite
|
Sign up to set email alerts
|

La economía colaborativa. Una aproximación al turismo colaborativo en España

Abstract: La actualmente denominada economía colaborativa, como modelo económico y social en el que los agentes comparten, de manera temporal, activos, bienes y servicios, en muchos casos infrautilizados, a cambio de dinero o de otros servicios, utilizando plataformas on line, está creciendo de manera imparable y se está introduciendo en sectores tradicionales como la producción de bienes y la prestación de servicios profesionales y financieros y, muy especialmente, en el sector turismo, en concreto en los subsectores d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
6
0
5
Order By: Relevance
“…As stated above, many Airbnb offers in residential tourism destinations might be homes and apartments that have already been used privately for tourism purposes, or offered for rent to tourists using other distribution channels. This applies particularly to the coast of Andalucía and Comunitat Valenciana, with the highest stocks of vacation rentals [97], and not so much to the archipelagos, where the numbers of hotel beds are much higher than those located in holiday apartments. Second homes also form a significant part of tourism accommodation in rural tourism areas [98], and our results suggest that such homes are also being commercialised through P2P platforms.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, many Airbnb offers in residential tourism destinations might be homes and apartments that have already been used privately for tourism purposes, or offered for rent to tourists using other distribution channels. This applies particularly to the coast of Andalucía and Comunitat Valenciana, with the highest stocks of vacation rentals [97], and not so much to the archipelagos, where the numbers of hotel beds are much higher than those located in holiday apartments. Second homes also form a significant part of tourism accommodation in rural tourism areas [98], and our results suggest that such homes are also being commercialised through P2P platforms.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies have emphasized the importance of the tourism industry for the Spanish economy and society. For instance, Rodríguez-Antón et al [56] reported that, despite the recent emergence of the phenomenon of the so-called collaborative economy, there has been enormous growth and future potential of the collaborative tourism model in the tourism industry. This implies that the tourism industry will continue to grow positively and contribute to the economic development of the country.…”
Section: Environmental Sustainability In Social Media Marketing Of Tourism Industry In Spainmentioning
confidence: 99%
“…La economía colaborativa es un concepto emergente, que actualmente está sometido a debate, recibiendo diversas denominaciones tales como consumo colaborativo (Algar, 2007;Botsman y Rogers, 2010), economía entre pares (Chase, 2015), entre otros, lo que hace difícil consensuar el término, y suscita diversidad de interpretaciones. Las distintas acepciones vienen derivadas del modelo de prestación de servicios, del tipo de participante o en función del uso de plataformas (Alfonso, 2016;Rodríguez-Antón et al, 2016;Alfaro, 2016).…”
Section: Introductionunclassified